A geometric tool for the analysis of position and force constraints in wave energy converters - Bacelli, Giorgio; Ringwood, John V. (Ocean engineering, 2013)
Most wave energy devices are subject to finite constraints on both the power take-off (PTO) stroke length and the maximum force that the PTO can tolerate. It is also often the case that greater stroke lengths can reduce the maximum force in the PTO and vice versa. Ultimately, some informed choice of PTO constraints must be made in order to ensure that PTO constraints are not violated and that the trade-off between position and force constraints is made in such as way that maximum energy is captured by the converter. This paper presents a tool to allow device developers to check the satisfaction of constraints for a given hydrodynamic model and set of sea conditions and, where constraints are not satisfied, shows how to relax the constraints to maximize energy capture. The tool is algebraic, requiring no simulation and the results are presented through intuitive geometrical constructs. Sample application results are presented for single- and two-body wave energy systems. •A discretization method is applied to express the system model as a linear system of equations.•Satisfaction of force and position constraints is done purely from the hydrodynamic model.•No simulation is required to evaluate constraints across a set of specific wave conditions.•The method is graphical and intuitively allows constraints to be adjusted to optimism power capture.•Multi-body devices are considered, with results for 1- and 2-body cases presented.